LEARNING LOSS IN GEOGRAPHY LEARNING: IMPLEMENTATION OF NATURAL DISASTER SIMULATION IN STATE SENIOR HIGH SCHOOL 60 JAKARTA - Nabilla, Lyzia; Hotimah, Oot; Sucahyanto, Sucahyanto (Program Studi Pendidikan Geografi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Samudra, 2024)
The COVID-19 pandemic forced changes in learning. Circular Letter of the Minister of Education and Culture No. 4/2020 emphasized that all activities, including learning, must be carried out from home to prevent the spread of the virus in schools. Online learning faces obstacles, especially in the implementation of practicums. This study aims to identify learning loss in grade XI IPS students at SMA Negeri 60 Jakarta during the COVID-19 pandemic through interviews and questionnaires. The results showed that disaster simulations in schools, especially in disaster-prone areas, play an important role in increasing student preparedness. The COVID-19 pandemic affected the implementation, but after the pandemic, the simulations were full again. Students, both online and offline, agreed that simulations should continue to be carried out. Students' high interest in simulations, both during and after the pandemic, showed a positive impact on understanding and enthusiasm for learning. In conclusion, disaster simulations in schools have a significant positive impact.